Effectiveness of the breast self-examination demonstration in improving knowledge, attitudes, and behavior of adolescent girls in senior high school in Samarinda - Rahayu, Eka Putri; Tonapa, Emelia; Chifdillah, Nino Adib (Universitas Gadjah Mada, 2023)
Purpose: This research aims to assess the effectiveness of the BSE demonstrations in enhancing the knowledge, attitudes, and behaviors of adolescent girls at SMA 1 Samarinda. Methods: This research employed a pre-experimental design with the One Group pre-post test. There was a population of 208 adolescent girls, with Slovin getting 94 samples. The students were selected by simple random sampling. Results: Knowledge p-value showed value (0,000) < α (0,05) while both attitudes and behavior values showed ρ-value (0,000) < α (0,05). There is an increase in knowledge, attitudes, and behavior before and after the BSE demonstration. Conclusion: The study concludes that BSE demonstrations effectively enhance adolescent girls' knowledge, attitudes, and behaviors.